Diagenesis Revealed by Fine‐Scale Features at Vera Rubin Ridge, Gale Crater, Mars. Issue 5 (11th May 2021) - Bennett, Kristen A.; Rivera‐Hernández, Frances; Tinker, Connor; Horgan, Briony; Fey, Deirdra M.; Edwards, Christopher; Edgar, Lauren A.; Kronyak, Rachel; Edgett, Kenneth S.; Fraeman, Abigail; Kah, Linda C.; Henderson, Marie; et al.
Abstract: Fine‐scale (submillimeter to centimeter) depositional and diagenetic features encountered during the Curiosity rover's traverse in Gale crater provide a means to understand the geologic history of Vera Rubin ridge (VRR). VRR is a topographically high feature on the lower north slope of Aeolis Mons, a 5‐km high stratified mound within Gale crater. We use high‐spatial resolution images from the Mars Hand Lens Imager (MAHLI) as well as grain sizes estimated with the Gini index mean score technique that uses ChemCam Laser‐Induced Breakdown Spectroscopy (LIBS) chemical data to constrain the postdepositional history of the strata exposed on this ridge. MAHLI images were used to examine the color, grain size, and style of lamination of the host rocks, as well as to explore the occurrence of nodules, diagenetic crystals, pits, and a variety of dark‐gray iron‐rich features. This survey revealed abundant and widespread diagenetic features within the rocks exposed on VRR and demonstrated that rock targets estimated to be coarser generally contain more diagenetic features than those estimated to have finer grains, which indicate that grain size may have influenced the degree and type of diagenesis. A subset of rocks within VRR are gray in color and exhibit the highest proportion of diagenetic features. We suggest that these targets experienced a different diagenetic history than the other rocks on VRR and hypothesize that redistribution and recrystallization of iron within specific intervals may have resulted in both the gray color and the abundance of dark‐gray iron‐rich diagenetic features. Plain Language Summary: We use high resolution images to identify submillimeter‐to‐centimeter scale features that resulted from either primary deposition or alteration of the rocks after the sediment was deposited at Vera Rubin ridge (VRR). VRR is located on the flank of Aeolis Mons, the 5‐km high mound that occupies the center of Gale crater on Mars. We find that the majority of these fine‐scale features were created after the initial deposition of sediment, when water existed in the subsurface and interacted with and altered the rocks. A subset of these features is dark gray in color and have iron‐rich compositions that suggest iron remobilization and recrystallization within the host rock. We find that rocks with larger grain sizes also show more postdepositional alteration features, suggesting that grain size influenced where water moved and interacted with rocks in the subsurface. Key Points: We investigate depositional and diagenetic features on Vera Rubin ridge using high‐spatial resolution images Observations of submillimeter‐to‐centimeter scale features indicate extensive diagenesis occurred in this area Subtle deviations in grain size likely contributed to the distribution and variability of diagenesis